Human Capital and Aggregate Income Differences in Mexico - Valero Gil, Jorge Noel; Valero, Magali (Taylor & Francis Group, 2021)
We study the relationship between differences in human capital and differences in product per worker of the federal entities of Mexico. We consider both quantity and quality of education in human capital formation, and use two methods for aggregating these two dimensions of education: a multiplicative and an additive model. Our measures of quality of education are constructed using the OECD’s Program for International Student Assessment (PISA) math achievement test scores in the additive model, and using the differences in the returns to education of the states in the multiplicative model. Our results are consistent to different methodologies and data sources. We find that variations in human capital explain upwards of 40% of the variations in state GDP per worker. Our results indicate that Mexican states should place more emphasis both in the quantity as well as quality of schooling, in order to improve the living standards of their population.